A non-woven fabric with wear-resistant and antibacterial structure

By applying reinforced antibacterial agents prepared by zinc-cerium hybrid micropowder and acrylate film-forming substrate on the nonwoven fabric, an improved functional coating is formed, which solves the problem of poor wear resistance and long-term antibacterial properties of the nonwoven fabric during the washing process, and achieves efficient antibacterial and wear resistance effects.

CN118207736BActive Publication Date: 2025-03-21GUANGZHOU SANLI NONWOVEN FABRICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410364194.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2025-03-21
Estimated Expiration
2044-03-28

AI Technical Summary

Technical Problem

Existing non-woven fabrics are prone to deform and fall off during washing, resulting in poor wear resistance and long-term antibacterial properties, limiting their application in non-disposable fabrics.

Method used

A functional coating with improved antibacterial properties and wear resistance is formed by combining an acrylate film-forming substrate by quaternization reaction and transesterification.

Benefits of technology

The wear resistance and long-acting antibacterial properties of non-woven fabrics have been significantly improved, with the antibacterial rate reaching more than 99.99%, the long-acting antibacterial rate reaching more than 99%, and the wear resistance reaches more than 40,000 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004763684060000091
    Figure BDA0004763684060000091
Patent Text Reader

Abstract

The present invention relates to a non-woven fabric with a wear-resistant and antibacterial structure, belonging to the technical field of composite non-woven fabrics. The non-woven fabric is composed of a base fabric and a functional coating, and the raw materials of the functional coating include, by weight, 100 parts of a film-forming emulsion, 3.2-4.5 parts of a reinforcing antibacterial agent, 4-5 parts of a accelerator, 0.3-0.4 parts of a photoinitiator, 0.2-0.3 parts of a defoamer, and 0.1-0.15 parts of a wetting agent; wherein the reinforcing antibacterial agent is a matrix of zinc-cerium hybrid micropowder, quaternization reaction is carried out with 3-chloropropanol and diethyl iminodiacetate to obtain an intermediate of a quaternary ammonium compound, which is loaded onto the surface of the zinc-cerium hybrid micropowder by its chelating property, and then in-situ ester exchange is carried out with the intermediate loaded on the surface by methallyl alcohol, and an acrylate structure modification is formed on the surface, which has a strong antibacterial effect, and can be cross-linked with an acrylate emulsion, greatly improving the wear resistance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite non-woven fabrics, and in particular relates to a non-woven fabric with a wear-resistant and antibacterial structure. Background Art

[0002] Nonwoven fabric is a kind of non-woven fabric, which is directly made of polymer chips, short fibers or filaments, and then formed into a net through airflow or machinery, and then reinforced by spunlace, needle punching or hot rolling, and finally finished to form a non-woven fabric. It is a new type of fiber product with soft, breathable and flat structure. Its biggest feature is that it does not produce fiber scraps and has a cotton feel. It also has a short process flow and high production efficiency. It is gradually replacing traditional textiles in many applications.

[0003] Similar to traditional textile fabrics, non-woven fabrics are easy to absorb liquid, and their porous structure makes it easier for bacteria to remain and grow. In the prior art, antibacterial agents are generally introduced into non-woven fabrics by methods such as impregnation or coating to give the non-woven fabrics a certain antibacterial property. There are many types of antibacterial agents currently used in textiles, and the overall antibacterial performance is good. However, antibacterial agents are easy to fall off, and the porous structure of non-woven fabrics makes them more likely to deform and fall off during the washing process, resulting in poor wear resistance and long-term antibacterial properties of non-woven fabrics, and their application in non-disposable fabrics is greatly limited. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a non-woven fabric with a wear-resistant and antibacterial structure.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A non-woven fabric with a wear-resistant and antibacterial structure, consisting of a base fabric and a functional coating, wherein the raw materials of the functional coating include, by weight:

[0007] 100 parts of film-forming emulsion, 3.2-4.5 parts of reinforcing antibacterial agent, 4-5 parts of accelerator, 0.3-0.4 parts of photoinitiator, 0.2-0.3 parts of defoaming agent and 0.1-0.15 parts of wetting agent.

[0008] The preparation method of the non-woven fabric with wear-resistant and antibacterial structure is as follows: the functional coating is prepared by mixing the raw materials, and then the functional coating is impregnated and attached to the base fabric, and then placed in a tunnel ultraviolet curing furnace for curing to form a functional coating in the base fabric to obtain the non-woven fabric.

[0009] Furthermore, the rolling margin is 8-11%.

[0010] Furthermore, the curing process parameters in the tunnel UV curing furnace are: zone 1, temperature 45-55°C, no irradiation, treatment time 5-8min; zone 2, temperature 60-70°C, UV irradiation intensity 220-300W / m 2 , treatment time is 3-5min; zone three, temperature is 50-60℃, UV radiation intensity is 180-260W / m 2 , the treatment time is 3-5min; in zone four, the temperature is 40-50℃, there is no irradiation, and the treatment time is 8-12min.

[0011] The enhanced antibacterial agent is prepared by the following method:

[0012] Step A1: diethyl iminodiacetate, 3-chloropropanol and anhydrous acetone are mixed, nitrogen is introduced for protection, the temperature is raised to 60-65° C. and refluxed, mechanical stirring is applied at 50-80 rpm, triethylamine is slowly added and reacted for 4-5 hours, and acetone is removed by rotary evaporation after the reaction is completed to obtain an intermediate;

[0013] Furthermore, the dosage ratio of diethyl iminodiacetate, 3-chloropropanol, triethylamine and anhydrous acetone is 0.1 mol: 0.25-0.3 mol: 10-15 mL: 45-60 mL. Under the promotion of triethylamine, 3-chloropropanol and diethyl iminodiacetate undergo quaternization reaction to form a quaternary ammonium compound.

[0014] Step A2: the intermediate and ethanol are mixed, and zinc-cerium hybrid powder is added, and the mixture is ultrasonically dispersed and allowed to stand for 12 hours, and the supernatant is removed and dried to obtain a precursor;

[0015] Furthermore, the dosage ratio of zinc-cerium hybrid micropowder, intermediate and ethanol is 100g:1.8-2.4g:150-200mL, and the nitrogen-oxygen structure in the intermediate molecule is loaded into the surface pores of the zinc-cerium hybrid micropowder through chelation.

[0016] Step A3: Mix the precursor, methallyl alcohol, phenol, aluminum chloride and toluene, introduce nitrogen protection, heat to 100-110°C, apply mechanical stirring at 120-150 rpm, react for 2.5-3 hours, and remove toluene by vacuum rotary evaporation after the reaction to obtain a reinforced antibacterial agent;

[0017] Furthermore, the amount ratio of the precursor, methallyl alcohol, phenol, aluminum chloride and toluene is 100g:12-16mL:25-30mg:5-8mg:80-100mL. Under the catalysis of aluminum chloride, methallyl alcohol and the intermediate molecules loaded on the surface of the precursor undergo in-situ ester exchange to form an acrylate structure modification on the surface.

[0018] The preparation method of the zinc-cerium hybrid micropowder is as follows: zinc chloride and cerium chloride are dissolved in oxalic acid solution, the water bath temperature is controlled at 45-55° C., 20-25 kHz ultrasonic dispersion is applied, ammonia water is slowly added to adjust the pH value to 4, stirring is switched to 80-120 rpm, ammonia water is added again to adjust the pH value to 6, and then the mixture is allowed to stand for 12 hours, the precipitate is dried, roasted and ground to obtain the zinc-cerium hybrid micropowder.

[0019] Furthermore, the molar ratio of zinc chloride to cerium chloride is 1:0.08-0.1, and the pH of the oxalic acid solution is not higher than 2.

[0020] Furthermore, the calcination process is set to: 120-150°C / 30-50min, 550-600°C / 15-20min, and cooled to room temperature with the furnace.

[0021] Beneficial effects of the present invention:

[0022] The invention discloses a non-woven fabric with a functional coating structure. The coating uses acrylate as a film-forming substrate and introduces a self-made enhanced antibacterial agent. The coating uses zinc-cerium hybrid micropowder as a matrix and uses 3-chloropropanol and diethyl iminodiacetate for quaternization reaction to obtain an intermediate of a quaternary ammonium compound. The intermediate is loaded on the surface of the zinc-cerium hybrid micropowder by utilizing its chelating property. Then, methallyl alcohol and the intermediate loaded on the surface are subjected to in-situ ester exchange to form an acrylate structure modification on the surface. The enhanced antibacterial agent introduces alcohol hydroxyl groups during the quaternization process, has certain hydrophilicity, is conducive to dispersion in an emulsion, and is conducive to the precipitation of antibacterial ions. The quaternary ammonium structure on the surface preferentially adsorbs bacteria and destroys their membrane structure, and then oxidizes under light conditions. Zinc produces photogenerated holes and photogenerated electrons, among which photogenerated holes can promote further oxidation and decomposition of internal substances of bacteria, thereby fully killing bacteria. In long-term experimental studies, it was found that a certain amount of cerium-doped zinc oxide can inhibit or the loss of photogenerated holes, and has a strong antibacterial effect compared to traditional zinc-based antibacterial agents; on the other hand, zinc-cerium hybrid micropowder, as an inorganic hard material, has a certain strengthening effect on the coating itself. The acrylate structure formed during the modification process can be cross-linked with the substrate, thereby strengthening the bonding strength between the zinc-cerium hybrid micropowder and the substrate, greatly improving the wear resistance of the coating, and at the same time fixing the strengthened antibacterial agent, the antibacterial components are not easily lost during long-term cleaning, and show good long-term antibacterial properties in the test. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1: Preparation of nonwoven fabric with wear-resistant and antibacterial structure, as follows:

[0025] 1) Preparation of cerium hybrid powder

[0026] Zinc chloride and cerium chloride were mixed in a molar ratio of 1:0.08, and oxalic acid solution with a pH value of 2 was added until dissolved. The water bath temperature was controlled at 45°C, and 20kHz ultrasonic dispersion was applied. Industrial ammonia water was slowly added at 10 drops / s to adjust the pH value to 4. The ultrasonic dispersion was stopped, and the stirring was switched to 80rpm. Ammonia water was added again to adjust the pH value to 6. The mixture was allowed to stand for 12 hours, the precipitate was dried, and calcined in a muffle furnace. The calcination process was controlled to be: 120°C / 50min, 550°C / 20min. The mixture was cooled to room temperature with the furnace, and ground to obtain zinc-cerium hybrid micropowder.

[0027] 2) Preparation of enhanced antimicrobial agents

[0028] Step A1: diethyl iminodiacetate, 3-chloropropanol and anhydrous acetone are mixed, nitrogen is introduced for protection, the temperature is raised to 60°C for reflux, mechanical stirring is applied at 50 rpm, triethylamine is slowly added within 2.5 hours, and the reaction is carried out for 5 hours. During the reaction, the amount ratio of diethyl iminodiacetate, 3-chloropropanol, triethylamine and anhydrous acetone is 0.1 mol: 0.25 mol: 15 mL: 45 mL. After the reaction, acetone is removed by rotary evaporation to obtain an intermediate.

[0029] Step A2: Mix the intermediate and ethanol, add zinc-cerium hybrid powder, and disperse them ultrasonically at 33kHz for 30 minutes, wherein the dosage ratio of zinc-cerium hybrid powder, intermediate and ethanol is 100g:1.8g:150mL. Let it stand for 12 hours, remove the supernatant and dry to obtain a precursor.

[0030] Step A3: Take the precursor, methallyl alcohol, phenol, aluminum chloride and toluene, mix them, introduce nitrogen protection, heat to 100°C, apply mechanical stirring at 120rpm, and react for 3h. During the reaction, the amount ratio of the precursor, methallyl alcohol, phenol, aluminum chloride and toluene is 100g:12mL:25mg:8mg:80mL. After the reaction, the toluene is removed by vacuum rotary evaporation to obtain an enhanced antibacterial agent.

[0031] 3) Preparation of non-woven fabric

[0032] Preparation of functional coating: raw materials are taken according to weight parts, 100 parts of film-forming emulsion, water-based textile emulsion of model TF-3601B, provided by Zhejiang Chuanhua Chemical Group, is used in the implementation process; 3.2 parts of enhanced antibacterial agent, prepared by this embodiment; 5 parts of accelerator, allyl glycidyl ether, chemically pure reagent, is used in the implementation process; 0.3 parts of photoinitiator, photoinitiator KIP-100F is used in the implementation process, provided by Nantong Synasia New Materials Co., Ltd.; 0.3 parts of defoamer, defoamer ZW-0108 is used in the implementation process, provided by Guangzhou Zhongwan New Materials Co., Ltd.; 0.1 parts of wetting agent, wetting agent GSK-588 is used in the implementation process, provided by Dongguan Gaosijin Lightweight Building Materials Manufacturing Co., Ltd.; add each raw material into a mixer and stir at 120rpm for 10min to obtain a functional coating.

[0033] Padding curing: Take the spunlace nonwoven fabric as the base fabric, then dip and pad the functional coating onto the base fabric, control the rolling rate to 8%, and then place it in a tunnel UV curing furnace. The process parameters in the furnace are controlled as follows: Zone 1, temperature 55°C, no irradiation, treatment time 5min; Zone 2, temperature 60°C, UV irradiation intensity 300W / m 2 , treatment time is 3min; zone 3, temperature is 50℃, UV irradiation intensity is 180W / m 2 , the treatment time is 5min; in zone four, the temperature is 40℃, there is no irradiation, the treatment time is 12min, the functional coating is cured to form a functional coating, and a non-woven fabric with a wear-resistant and antibacterial structure is obtained.

[0034] Example 2: Preparation of a nonwoven fabric with a wear-resistant and antibacterial structure, as follows:

[0035] 1) Preparation of cerium hybrid powder

[0036] Zinc chloride and cerium chloride were mixed in a molar ratio of 1:0.1, and oxalic acid solution with a pH value of 2 was added until dissolved. The water bath temperature was controlled at 55°C, and 25kHz ultrasonic dispersion was applied. Industrial ammonia water was slowly added at 10 drops / s to adjust the pH value to 4. The ultrasonic dispersion was stopped, and the stirring was switched to 120rpm. Ammonia water was added again to adjust the pH value to 6. The mixture was allowed to stand for 12 hours, the precipitate was dried, and calcined in a muffle furnace. The calcination process was controlled to be: 150°C / 30min, 600°C / 15min. The mixture was cooled to room temperature with the furnace, and ground to obtain zinc-cerium hybrid micropowder.

[0037] 2) Preparation of enhanced antimicrobial agents

[0038] Step A1: diethyl iminodiacetate, 3-chloropropanol and anhydrous acetone are mixed, nitrogen protection is introduced, the temperature is raised to 65°C and refluxed, mechanical stirring is applied at 80 rpm, triethylamine is slowly added within 2 hours, and the reaction is carried out for 4 hours. During the reaction, the amount ratio of diethyl iminodiacetate, 3-chloropropanol, triethylamine and anhydrous acetone is 0.1 mol: 0.3 mol: 10 mL: 60 mL. After the reaction, acetone is removed by rotary evaporation to obtain an intermediate.

[0039] Step A2: Mix the intermediate and ethanol, add zinc-cerium hybrid powder, and disperse them ultrasonically at 33kHz for 30 minutes, wherein the dosage ratio of zinc-cerium hybrid powder, intermediate and ethanol is 100g:2.4g:200mL. Let it stand for 12 hours, remove the supernatant and dry to obtain a precursor.

[0040] Step A3: Take the precursor, methallyl alcohol, phenol, aluminum chloride and toluene, mix them, introduce nitrogen protection, heat to 110°C, apply mechanical stirring at 150rpm, and react for 2.5h. During the reaction, the amount ratio of the precursor, methallyl alcohol, phenol, aluminum chloride and toluene is 100g:16mL:30mg:5mg:100mL. After the reaction, the toluene is removed by vacuum rotary evaporation to obtain an enhanced antibacterial agent.

[0041] 4) Preparation of non-woven fabric

[0042] Prepare functional coating: take raw materials according to weight parts, 100 parts of film-forming emulsion; 4.5 parts of enhanced antibacterial agent prepared in this embodiment; 4 parts of accelerator; 0.4 parts of photoinitiator; 0.2 parts of defoaming agent; 0.15 parts of wetting agent; add all raw materials into a mixer and stir at 120 rpm for 10 min to obtain functional coating.

[0043] Padding curing: Take the spunlace nonwoven fabric as the base fabric, and then pad the functional coating onto the base fabric, control the padding rate to 11%, and then place it in a tunnel UV curing furnace. The process parameters in the furnace are controlled as follows: Zone 1, temperature 45°C, no irradiation, treatment time 8min; Zone 2, temperature 70°C, UV irradiation intensity 220W / m 2 , treatment time is 5min; zone three, temperature is 60℃, UV irradiation intensity is 260W / m 2 , the treatment time is 3min; in zone four, the temperature is 50℃, there is no irradiation, the treatment time is 8min, the functional coating is cured to form a functional coating, and a non-woven fabric with a wear-resistant and antibacterial structure is obtained.

[0044] Example 3: Preparation of nonwoven fabric with wear-resistant and antibacterial structure, as follows:

[0045] 1) Preparation of cerium hybrid powder

[0046] Zinc chloride and cerium chloride were mixed in a molar ratio of 1:0.09, and oxalic acid solution with a pH value of 2 was added until dissolved. The water bath temperature was controlled at 52°C, and 25kHz ultrasonic dispersion was applied. Industrial ammonia water was slowly added at 10 drops / s to adjust the pH value to 4. The ultrasonic dispersion was stopped and stirred at 120rpm. Ammonia water was added again to adjust the pH value to 6. The mixture was allowed to stand for 12 hours, the precipitate was dried, and calcined in a muffle furnace. The calcination process was controlled to be: 130°C / 40min, 580°C / 17min. The mixture was cooled to room temperature with the furnace and ground to obtain zinc-cerium hybrid micropowder.

[0047] 2) Preparation of enhanced antimicrobial agents

[0048] Step A1: diethyl iminodiacetate, 3-chloropropanol and anhydrous acetone are mixed, nitrogen protection is introduced, the temperature is raised to 60°C and refluxed, mechanical stirring is applied at 80 rpm, triethylamine is slowly added within 2.2 hours, and the reaction is carried out for 4.5 hours. During the reaction, the amount ratio of diethyl iminodiacetate, 3-chloropropanol, triethylamine and anhydrous acetone is 0.1 mol: 0.28 mol: 12 mL: 55 mL. After the reaction, acetone is removed by rotary evaporation to obtain an intermediate.

[0049] Step A2: Mix the intermediate and ethanol, add zinc-cerium hybrid powder, and disperse them ultrasonically at 33kHz for 30 minutes, wherein the dosage ratio of zinc-cerium hybrid powder, intermediate and ethanol is 100g:2.1g:170mL. Let it stand for 12 hours, remove the supernatant and dry to obtain a precursor.

[0050] Step A3: Take the precursor, methallyl alcohol, phenol, aluminum chloride and toluene, mix them, introduce nitrogen protection, heat to 110°C, apply mechanical stirring at 150rpm, and react for 2.8h. During the reaction, the amount ratio of the precursor, methallyl alcohol, phenol, aluminum chloride and toluene is 100g:15mL:28mg:6mg:90mL. After the reaction, the toluene is removed by vacuum rotary evaporation to obtain an enhanced antibacterial agent.

[0051] 5) Preparation of non-woven fabric

[0052] Prepare functional coating: take raw materials according to weight parts, 100 parts of film-forming emulsion; 3.9 parts of enhanced antibacterial agent prepared in this embodiment; 4 parts of accelerator; 0.35 parts of photoinitiator; 0.2 parts of defoaming agent; 0.12 parts of wetting agent; add all raw materials into a mixer and stir at 120 rpm for 10 min to obtain functional coating.

[0053] Padding curing: Take the spunlace nonwoven fabric as the base fabric, then dip and roll the functional coating onto the base fabric, control the rolling rate to 10%, and then place it in a tunnel UV curing furnace. The process parameters in the furnace are controlled as follows: Zone 1, temperature 50°C, no irradiation, treatment time 7min; Zone 2, temperature 65°C, UV irradiation intensity 260W / m 2 , treatment time is 4min; zone 3, temperature is 55℃, UV irradiation intensity is 220W / m 2 , treatment time is 4min; in zone four, temperature is 45℃, no irradiation, treatment time is 10min, the functional coating is cured to form a functional coating, and a non-woven fabric with wear-resistant and antibacterial structure is obtained.

[0054] In the comparative example, a zinc antibacterial agent and a quaternary ammonium salt antibacterial agent are compounded to replace the reinforced antibacterial agent to prepare a non-woven fabric, as follows:

[0055] Prepare functional coating: take raw materials according to weight parts, 100 parts of film-forming emulsion; 3.4 parts of zinc antibacterial agent, model ZN90, provided by Nanjing Tianshi Landun Biotechnology Co., Ltd.; 0.7 parts of quaternary ammonium antibacterial agent, model WD-15SG, provided by Wuxi Yuda Fine Chemical Co., Ltd.; 4.5 parts of accelerator; 0.4 parts of photoinitiator; 0.3 parts of defoaming agent; 0.1 parts of wetting agent; add all raw materials into a mixer, stir at 120 rpm for 10 min to obtain functional coating.

[0056] Padding curing: Take the spunlace nonwoven fabric as the base fabric, then dip and roll the functional coating onto the base fabric, control the rolling rate to 10%, and then place it in a tunnel UV curing furnace. The process parameters in the furnace are controlled as follows: Zone 1, temperature 50°C, no irradiation, treatment time 7min; Zone 2, temperature 65°C, UV irradiation intensity 260W / m 2 , treatment time is 4min; zone 3, temperature is 55℃, UV irradiation intensity is 220W / m 2 , the treatment time is 4min; in zone four, the temperature is 45℃, there is no irradiation, the treatment time is 10min, the functional coating is cured to form a functional coating to obtain a non-woven fabric.

[0057] Preparation of test bacterial solution: Gram-positive bacteria, Staphylococcus aureus, and Gram-negative bacteria, Escherichia coli, were used as test bacteria and prepared to a concentration of 4×10 5CFU / mL of bacterial solution for standby; take Example 1 to Example 3 and the comparative example and test the antibacterial rate according to GB / T 20944.3-2008 standard; use the deep cleaning detergent provided by Blue Moon Group Holdings Co., Ltd. to repeatedly soak the non-woven fabric, soak for 2 hours + wash for 30 minutes + dry with fluorescent lamp for 3 hours, repeat 50 times, test the antibacterial rate again, and calculate the long-term antibacterial rate = (first antibacterial rate - antibacterial rate after repeated soaking) / first antibacterial rate × 100%; refer to GB / T 21196.2-2007 standard to test the wear resistance, and the specific test data are shown in Table 1:

[0058] Table 1

[0059]

[0060] It can be seen from the data in Table 1 that the non-woven fabric prepared in the embodiment of the present invention has an antibacterial rate of more than 99.99% against Staphylococcus aureus and Escherichia coli, and a long-term antibacterial rate of more than 99%, showing excellent antibacterial effect, and the wear resistance times reaches more than 40,000 times, which is much higher than the existing coated composite non-woven fabrics.

[0061] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0062] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A non-woven fabric with a wear-resistant and antibacterial structure, consisting of a base fabric and a functional coating, characterized in that: The raw materials of the functional coating include, by weight: 100 parts of film-forming emulsion, 3.2-4.5 parts of enhanced antibacterial agent, 4-5 parts of accelerator, 0.3-0.4 parts of photoinitiator, 0.2-0.3 parts of defoamer and 0.1-0.15 parts of wetting agent; Wherein, the enhanced antibacterial agent is prepared by the following method: Step A1: diethyl iminodiacetate, 3-chloropropanol and anhydrous acetone are mixed, nitrogen is introduced, the temperature is raised to 60-65°C and refluxed, and triethylamine is slowly added with stirring to react for 4-5 hours. After the reaction is completed, acetone is removed by rotary evaporation to obtain an intermediate; Step A2: the intermediate and ethanol are mixed, and zinc-cerium hybrid powder is added, and the mixture is ultrasonically dispersed and allowed to stand for 12 hours, and the supernatant is removed and dried to obtain a precursor; Step A3: Mix the precursor, methallyl alcohol, phenol, aluminum chloride and toluene, introduce nitrogen protection, heat to 100-110°C, stir and react for 2.5-3h, and remove toluene by vacuum rotary evaporation after the reaction to obtain a reinforced antibacterial agent; The film-forming emulsion is an acrylic emulsion.

2. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 1, characterized in that: The usage ratio of diethyl iminodiacetate, 3-chloropropanol, triethylamine and anhydrous acetone is 0.1 mol: 0.25-0.3 mol: 10-15 mL: 45-60 mL.

3. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 2, characterized in that: The dosage ratio of zinc-cerium hybrid micropowder, intermediate and ethanol is 100g:1.8-2.4g:150-200mL.

4. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 3, characterized in that: The usage ratio of the precursor, methallyl alcohol, phenol, aluminum chloride and toluene is 100 g: 12-16 mL: 25-30 mg: 5-8 mg: 80-100 mL.

5. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 1, characterized in that: The preparation method of zinc-cerium hybrid micropowder is as follows: zinc chloride and cerium chloride are dissolved in oxalic acid solution, the temperature of the water bath is controlled at 45-55°C, 20-25kHz ultrasonic dispersion is applied, ammonia water is slowly added to adjust the pH value to 4, stirring is switched to 80-120rpm, ammonia water is added again to adjust the pH value to 6, and then the mixture is allowed to stand for 12 hours, the precipitate is dried, roasted and ground to obtain zinc-cerium hybrid micropowder.

6. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 5, characterized in that: The molar ratio of zinc chloride to cerium chloride is 1:0.08-0.1, and the pH of the oxalic acid solution is not higher than 2.

7. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 5, characterized in that: The calcination process was set as: 120-150°C / 30-50min, 550-600°C / 15-20min, and cooled to room temperature with the furnace.

8. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 1, characterized in that: The specific preparation method is: mix the raw materials evenly to prepare the functional coating, then immerse and roll the functional coating into the base fabric, and then place it in a tunnel UV curing furnace for curing to form a functional coating in the base fabric to obtain a non-woven fabric.

9. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 8, characterized in that: The rolling rate of dip rolling is 8-11%.

10. The nonwoven fabric with wear-resistant and antibacterial structure according to claim 8, characterized in that: The curing process parameters in the tunnel UV curing furnace are: Zone 1, temperature 45-55°C, no irradiation, processing time 5-8min; Zone 2, temperature 60-70°C, UV irradiation intensity 220-300W / m 2 , treatment time is 3-5min; zone three, temperature is 50-60℃, UV radiation intensity is 180-260W / m 2 , the treatment time is 3-5min; in zone four, the temperature is 40-50℃, there is no irradiation, and the treatment time is 8-12min.

Citation Information

Patent Citations

  • Antibacterial non-woven fabric and preparation method thereof

    CN112227078A

  • Witch hazel soothing and bacteriostatic sanitary wet tissue and production process thereof

    CN114848551A